1987
DOI: 10.1254/jjp.44.43
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Mechanism of Protection by Polyamines against Gastric Damage Induced by Acidified Ethanol in Rats: Polyamine Protection May Depend on Its Antiperoxidative Properties

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…In the present study, oral administration of celery extract inhibited the gastric damage caused by ethanol and strong alkali, the most commonly employed tests in the evaluation of anti-ulcer/cytoprotective activity (Oliveira et al, 2004). It is suggested that oxygen radicals may contribute to the induction of ethanol and other necrotizing agents-induced gastric mucosal lesions (Trier et al, 1987;Matsumoto et al, 1992) and anti-oxidants are protective against the damage caused by oxidants (Mizui et al, 1987;Farina et al, 1998). Ethanol has been shown to deplete the level of non-protein sulfhydryl content in stomach tissues and its restoration appears to be important in gastroprotection since they provide a substrate for free radicals to replenish GSH stores (Trier et al, 1987).…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, oral administration of celery extract inhibited the gastric damage caused by ethanol and strong alkali, the most commonly employed tests in the evaluation of anti-ulcer/cytoprotective activity (Oliveira et al, 2004). It is suggested that oxygen radicals may contribute to the induction of ethanol and other necrotizing agents-induced gastric mucosal lesions (Trier et al, 1987;Matsumoto et al, 1992) and anti-oxidants are protective against the damage caused by oxidants (Mizui et al, 1987;Farina et al, 1998). Ethanol has been shown to deplete the level of non-protein sulfhydryl content in stomach tissues and its restoration appears to be important in gastroprotection since they provide a substrate for free radicals to replenish GSH stores (Trier et al, 1987).…”
Section: Discussionmentioning
confidence: 54%
“…HCl/EtOH-induced gastric ulceration has been indicated to be due to neutrophil-generated ROS [23]. In addition, this ulcer has been indicated to be due to impairments in defensive factors such as mucus [24]. Diacerein inhibited the HCl/ EtOH-induced gastric ulceration in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this aspect, it is known that amines can yield derivatives of phospholipid hydroperoxides in the presence of haem (lio & Yoden, 1988). At a cellular level, the antiperoxidative properties of polyamines were correlated with their protective effect against gastric lesions induced by acidified ethanol (Mizui et al, 1987).…”
Section: Interaction Of Polyamines With Membrane Componentsmentioning
confidence: 99%